Prognostic value of plasma Amyloid‐β 42/40 ratio in early and pre‐clinical AD. (20th December 2022) - Vogelgsang, Jonathan; Klafki, Hans; Morgado, Barbara; Jahn‐Brodmann, Anke; Esselmann, Hermann; Bauer, Chris; Schuchhardt, Johannes; Peters, Oliver; Priller, Josef; Schneider, Anja; Fliessbach, Klaus; Jessen, Frank; et al.
Abstract: Background: In 2021 Adacanumab, the first antibody that might potentially treat causal neuropathology associated to Alzheimer's disease (AD), was approved by the FDA. However, early, most likely pre‐cognitive treatment is required raising a high need for early and low‐invasive diagnostic biomarker. Here, we present plasma Amyoid‐beta (Aβ) measurements in a large longitudinal observational study from the German Center for Neurodegenerative Diseases (DZNE, DZNE‐Longitudinal Cognitive Impairment and Dementia (DELCODE) study). Method: Plasma Aβ40 and Aβ42 of 1049 baseline samples from the DELCODE cohort were measured in a semi‐automated fashion according to our recently published protocol. Aβ immunoprecipitation and Mesoscale immuno‐measurement were controlled for batch effects. All samples were well balanced and Mesoscale Aβ measurements were performed in two technical replicates on the same assay plate. 41 samples with a coefficient of variation > 10% between the two technical replicates were re‐measured. Corresponding CSF and plasma Aβ measurements were available for 377 samples for further downstream analysis. Result: Interassay variability from a QC sample using 6 replicates was 8.3%, 8.0%, and 6.9% for Aβ40, Aβ42, and the Aβ42/40 ratio, respectively. CSF and plasma Aβ42 and Aβ42/40 ratio correlated with r=0.169 (p<0.001) and r=0.466 (p<0.0001), respectively. No correlation was observed for Aβ40. Plasma Aβ42/40 was able to distinguish samples from donors with a CSF Aβ42/40 ratio classified as pathological or normal with an AUC of 0.82. ApoE inclusion increased the AUC for plasma Aβ42/40 to 0.87 with a specificity of 0.73 and a sensitivity of 0.87. Importantly, plasma Aβ42/40 was not only able to differentiate participants with high vs. low CSF Aβ42/40 in general, but also predicted Aβ status in patients with milder or no cognitive impairments: in controls, the AUC for the plasma Aβ42/40 ratio was 0.78, in SCI 0.76, and in MCI 0.71. There was only one dementia case with a normal CSF Aβ profile, thus no further comparison could be performed for donors in dementia stage. Conclusion: Plasma Aβ can differentiate CSF pathological vs normal AD patients. Further analysis including follow‐up data to identify the early predictive value of plasma Ab will be performed including neurocognitive measurements to include all plasma Aβ measurements.